Predictors of occurrence of shockable rhythm and return of spontaneous circulation in patients with witnessed cardiac arrest - Ristić, Jovana; Medić, Sara; Lazić, Aleksandra; Ranđelović , Suzana; Šušković Bosančić , Rajka; Bandulaja, Marina; Vasilić, Milica (Journal Resuscitatio Balcanica, 2025)
Introduction: Out-of-hospital cardiac arrest (OHCA) represents a major global health concern, with survival rates at hospital discharge remaining low (on average 8%). Survival outcomes depend heavily on several factors, such as the location of the arrest, time to return of spontaneous circulation (ROSC), patient demographics and the type of initial cardiac rhythm.The Aim: Given the complexities of OHCA outcomes, this study aims to identify independent predictors of shockable rhythm, any ROSC, and ROSC on hospital admission in witnessed OHCA cases. Material and Methods: EuReCa_Serbia is part of the international, prospective, multicenter EuReCa ONE study of survival (epidemiology, treatment and outcomes) of patients who experienced OHCA in Europe. The inclusion criterion was OHCA taken care of by the EMS team. Pediatric patients as well as patients with cardiac arrest of non-cardiogenic cause (including traumatic cardiac arrest) were included in the analysis. The created database consisted of information defined by the unique protocol of the EuReCa ONE study in the period from October 1, 2014 to December 31, 2021. Results: Causal-consecutive association of potential predictors of shockable initial rhythm, return of spontaneous circulation and hospital admission was examined using univariable and multivariable binary logistic regression analysis. We found that OHCAs in areas with over 100,000 inhabitants and those occurring at a patient’s residence were associated with a significantly lower likelihood of shockable rhythms (62,3% and 53,5% less likely), while older age and cardiogenic cause increased the chance of shockable rhythms (1.7 and 10.6 times more likely). The independent predictors for ROSC on hospital admission closely mirrored those for any ROSC: shockable rhythms increased the likelihood of ROSC on admission by 3.8 times, while urban areas and residential locations reduced the chances (69.4% and 50.4% less likely). Conclusion: In conclusion, our study identified several independent predictors influencing the occurrence of shockable rhythm, any ROSC, and ROSC on admission in witnessed OHCA cases. Further research is needed to explore these interactions in diverse populations and regions, as well as to develop tailored interventions that can improve pre-hospital and in-hospital outcomes